The Impacts of Head Loss on the Bulb Turbine’s Hydropower Utilization and Running Performance - Zhenggui LI; Fengyu YANG; Dehong WANG; Ruijie MA (Institute of Advanced Engineering and Science, 2014)
Because of the truth that the earth resources become increasingly tense, Low-head bulb turbine group was relatively fast developed and constructed in a time.The number of its running on the various types of rivers has reached a certain degree.However,its main problems are water utilization and running performance are not optimal.Its stand-alone capacity is small,therefore the problem has not attracted attention in the academia.In this paper,we based on the typical bulb turbine as the research object,using UG to the whole flow passage of mathematical modeling,based on the model of the operating characteristic curve, through Ansys software analyzes unit internal flow field calculation,and found that in a combination of guide vane and the blade opening, the head loss is the major cause of water can not efficient conversion.When increase the effective water head,can improve the output and efficiency of unit. Further analysis of the whole flow passag，the runner outlet flow patterns and the runner blade pressure,finding that the conditions can improve the turbines running performance at the same time.In the real machine test and long running practice, the above calculation results were verified. DOI : http://dx.doi.org/10.11591/telkomnika.v12i4.4891